Epstein Barr Virus Exploits Genetic Susceptibility to Increase Multiple Sclerosis Risk - Fabienne Läderach (MDPI AG, 2021)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS) for which both genetic and environmental risk factors have been identified. The strongest synergy among them exists between the MHC class II haplotype and infection with the Epstein Barr virus (EBV), especially symptomatic primary EBV infection (infectious mononucleosis) and elevated EBV-specific antibodies. In this review, we will summarize the epidemiological evidence that EBV infection is a prerequisite for MS development, describe altered EBV specific immune responses in MS patients, and speculate about possible pathogenic mechanisms for the synergy between EBV infection and the MS-associated MHC class II haplotype. We will also discuss how at least one of these mechanisms might explain the recent success of B cell-depleting therapies for MS. While a better mechanistic understanding of the role of EBV infection and its immune control during MS pathogenesis is required and calls for the development of innovative experimental systems to test the proposed mechanisms, therapies targeting EBV-infected B cells are already starting to be explored in MS patients.